Curadoria transmídia em festivais audiovisuais e estudo de caso pós-pandêmico do MixBrasil - Fischer, André (2023)
Technological innovations have caused profound transformations in the way audiovisual content is produced, understood, consumed, and programmed. The restrictions resulting from the COVID-19 pandemic have significantly catalyzed the metamorphoses that were already transforming the foundations of both the film industry and the entire festival ecosystem. This research defines the concept of transmedia curation and explores the interaction between taste, politics, and programming throughout history, and considers the role of algorithms and the impact of curatorial choices on festivals. The analysis of the term and its application in audiovisual festivals is carried out using practical experiences from over 30 years on the MixBrasil Festival, particularly from 2020 onwards. The study reflects on the origin and consolidation of the film festival circuit, the effects of emerging technologies on the dynamics of festivals, and discusses the challenges faced by the audiovisual industry and potential future directions. It highlights the technological evolution of Brazilian LGBT+ themed audiovisual production, the adoption of digital platforms, and the adaptation of festival programming during and after the pandemic. Hashtags are identified as an initial literacy tool for both the general public and programming teams. This dissertation, written using the principles of inclusive language, addresses the path of incorporating immersive experiences, using extended realities (XR) such as virtual reality (VR) and augmented reality (AR), by analyzing the confluence between curation, technological innovation, and the specificities of LGBT+ festivals. In conclusion, the dissertation presents perspectives on the evolution of audiovisual festivals as a comprehensive phenomenon, as well as methodologies and practices for implementing transmedia curation in audiovisual festivals, contributing to the development and improvement of these events in the contemporary landscape.